Employee Information System Design Of KAI Property Management Limited Liability Company Medan Based On Android - Nurlangga, Rama Nopan; Dedi Irawan, Muhammad; Prabowo, Eko Heri (Ali Institute or Research and Publication, 2023)
Indonesian Railways Limited Liability Company Property Management or KAI Property Management Limited Liability Company Medan is one of the subsidiaries of KAI Limited Liability Company which was established in 2009 with core businesses in the fields of construction, property, trade and maintenance of railway infrastructure and its supporting facilities. In the process of importing employee data at KAI Property Management Limited Liability Company Medan still uses manuals, so to make it easier to collect data, it makes an employee information system that is easy to use and quite safe. This study used waterfall, uml, and blackbox methods. The waterfall method consists of analysis, design, development, testing, and deployment, and uml used usecase diagrams, activity diagrams, and sequence diagrams. The results of this study are in the form of an information system design that uses codular as an android application maker that can help in terms of processing office employee data.